P427 Efficacy and safety of vedolizumab and adalimumab in Asian adults with moderately to severely active ulcerative colitis: Post-hoc analysis of the VARSITY trial. (27th May 2021) - Kim, J S; Leung, W K; Wu, D C; Lindner, D; Fadeeva, O; Demuth, D
Abstract: Background: The VARSITY trial, the first head-to-head study comparing the efficacy and safety of biologics in patients with moderately to severely active ulcerative colitis (UC), demonstrated superior clinical remission with vedolizumab (VDZ) versus adalimumab (ADA) at week 52. This post-hoc analysis describes outcomes in patients from Asia included in the VARSITY trial. Methods: Adult patients with moderately to severely active UC (Mayo score 6–12; endoscopic sub-score ≥2), refractory to conventional therapies and anti–tumour necrosis factor-naïve or -experienced (exposure capped at 25%) were included. This analysis focussed on patients from Hong Kong, Taiwan and South Korea. Patients were randomised (1:1) to receive intravenous (IV) VDZ (300mg) and subcutaneous (SC) placebo on day 1 of weeks 2, 6, 14, 22, 30, 38 and 46 or SC ADA, at weeks 1 (total dose:160mg) and 2 (80mg) and every 2 weeks (40mg) plus IV placebo thereafter until week 50. The primary endpoint was clinical remission at week 52. Secondary endpoints included rates of endoscopic improvement, corticosteroid (CS)-free remission and histological remission at week 52. Patients with missing endpoint assessment at week 52 were considered non-responders. Data were analysed descriptively. Results: A total of 45 patients (VDZ: n=21; ADA: n=24) were included. At baseline (VDZ and ADA, respectively), the mostly male population (71.4% and 58.3%) had a mean (SD) age of 46.4 (14.7) and 40.4 (15.1) years; severe disease: 33.3% and 54.2%; mean (SD) disease duration: 6.8 (5.5) and 5.4 (3.5) years; and were biologic-naïve: 85.7% and 79.2%. At week 52, a higher rate of clinical remission was achieved in VDZ- vs. ADA-treated patients (28.6% vs. 16.7%; Table). Adverse events (AEs) occurred in 71.4% (VDZ) and 87.5% (ADA) of patients; serious AEs occurred in 4.8% (VDZ) and 16.7% (ADA) of patients. AEs led to study drug discontinuation in 4.8% (VDZ) and 8.3% (ADA) of patients; no deaths occurred. Conclusion: Patients from Asian countries with moderately to severely active UC achieved higher rates of clinical, CS-free, and histological remission as well as endoscopic improvement with VDZ vs. ADA. VDZ and ADA were both generally safe and well tolerated. Descriptive trends were consistent with findings in the larger VARSITY cohort.